Psychometric Properties of the Persian Version of Movement Assessment Battery for Children Checklist in 6- to 7-Year-Old Children - Mahsa Alaei; Rokhsareh Badami (Vesnu Publications, 2020)
Introduction: The Movement Assessment Battery for Children (MABC) checklist has been designed to investigate children's movement disorders at school; however, the validation characteristics of this checklist in Iran have not been evaluated. Therefore, the present study aimed to evaluate the psychometric characteristics of MABC checklist. Materials and Methods: The participants in this study comprised 181 six-year-old children (87 girls and 94 boys) and 166 seven-year-old children (89 girls and 77 boys) from Isfahan City, Iran. Their sports teachers completed the MABC checklist. To measure concurrent validity, motor skills of 233 of these children were assessed using MABC. To measure construct validity, confirmatory factor analysis and convergent validity [Average Variance Extracted (AVE)] were used. Moreover, to measure reliability, Cronbach's alpha, composite reliability, and test-retest reliability were used. Results: AVE indicator was used to evaluate subscales of child stationary/environment stable, child moving/environment stable, child stationary/environment changing, child moving/environment changing, and behavioral problems related to motor difficulties. The overall scores obtained were 0.51, 0.5, 0.53, 0.54, 0.49, and 0.5, respectively. Cronbach's alpha and composite reliability were 0.79 and 0.84 for the subscales of "the child is stationary and the environment is stable", 0.85 and 0.88 for "the child is moving and the environment is stable", 0.87 and 0.84 for "the child is stationary and the environment is changing", 0.89 and 0.91 for "the child is moving and the environment is changing", 0.81 and 0.82 for "behaviors related to physical activity", and 0.92 and 0.94 for all the subscales. The correlation coefficient of MABC with MABC checklist was 0.37, which was significant at P < 0.001. Conclusion: The data indicate that MABC checklist is valid and reliable for 6- to 7-year-old children. Therefore, teachers are recommended to use this checklist in investigating children's movement disorders in primary school children.